Analisis Perbandingan Frekuensi Transaksi Tunai, E-Wallet, dan Transfer Bank dalam Aktivitas Harian Masyarakat - Aribbah Fitroti; Haifa Nur Jubaidah; Rifka Aqila; Yasir Ahmad Muyassar; Mia Lasmi Wardiyah (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
The rapid advancement of digital technology has led to significant changes in how people conduct financial transactions, particularly the shift from cash payments to digital methods that are viewed as more efficient, faster, and safer. This study aims to analyze differences in the frequency of using three types of financial transactions cash, e-wallets, and bank transfers in daily life. A quantitative descriptive-comparative approach was applied, involving 47 respondents selected through purposive sampling. The instruments were tested for validity and reliability before analysis. Data were examined using the Friedman test to assess differences in usage frequency among the three methods. The findings show a significant difference in frequency, with e-wallets being the most used, followed by bank transfers, and then cash. These results suggest that people now prioritize convenience, speed, and accessibility in financial activities. The implications highlight the need for financial institutions and payment providers to enhance digital security systems and improve service accessibility. Small business operators are encouraged to adapt to changing consumer preferences that increasingly favor digital payments. Furthermore, improving digital financial literacy is essential to support broader financial inclusion. This study also provides recommendations for policymakers to expand access to digital financial services, especially for underserved communities.